THE CORRELATION OF KNOWLEDGEMENT RATING AND PERSONAL HYGIENE WITH PEDICULOSIS CAPITIS AMONG SEVENTH, EIGHTH, AND NINTH GRADE OF FEMALE STUDENTS AT YUSUF ABDUSSATAR ISLAMIC BOARDING SCHOOL - Nurbayani, Karina Putri; Mariam, Lysa; Mardiah, Aena; Anditiarina, Dasti (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Pediculosis capitis among the children in school can affect learning performance. These children also suffer from sleep disturbances at night due to itching, social stigma, embarrassment and low self-esteem. Pediculosis capitis is especially prevalent in boarding schools with knowledge and personal hygiene being the main risk factors for pediculosis capitis. This research was conducted to determine the correlation of knowledge rate and personal hygiene with pediculosis capitis in seventh, eighth, and ninth grade of female students at Yusuf Abdussatar Islamic Boarding School. Method. This research used an observational analytic quantitative method with a cross sectional study design. The sampling technique used stratified random sampling. The research was conducted at Yusuf Abdussatar Islamic Boarding School on October 15, 2022. The research sample was 188 respondents. Result and Analysis. The data obtained were analyzed with the Chi-Square correlation test. The limit of significance value is p-value <0.05. Bivariate analysis results based on the level of knowledge obtained a p-value of 0.650 (p-value> 0.05) and based on personal hygiene p-value of 0.295 (p-value> 0.05). Discussion. There was no significant relationship between the knowledge rate and personal hygiene with pediculosis capitis in seventh, eighth, and ninth grade of female students at Yusuf Abdussatar Islamic Boarding School.